Design of a 75 K. W. power station - Donly, Max C.; Walker, Carroll (My University, 1908)
Introduction: The first consideration in installing a power plant is the cost. Whether or not the money invested will bring returns, is the proposition that outweighs all others. This resolves itself into the supply and demand for power and the cost of producing the power and installing the necessary machinery.
Citation: Donly, Max C. and Walker, Carroll. Design of a 75 K. W. power station. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Power Stations; Energy; Engineering; Architecture; Graduating theses; Senior theses; Theses